Higher body mass index indicated better overall survival in pancreatic ductal adenocarcinoma patients: a real-world study of 2010 patients - Ningzhen Fu; Yu Jiang; Kai Qin; Hao Chen; Xiaxing Deng; Baiyong Shen (BMC Cancer, 2021)
Abstract Background The association between body mass index (BMI) and the overall survival (OS) of pancreatic ductal adenocarcinoma (PDAC) patients remains controversial and unclear, Method A total of 2010 patients from a high-volume center were enrolled in the study. The OS of PDAC patients was evaluated based on restricted cubic spline (RCS), propensity score (PS) and multivariable risk adjustment analyses. Result BMI was linearly related to the OS (total P = 0.004, nonlinear P = 0.124). BMI was analyzed as categorical data based on X-tile software-defined cutoffs and World Health Organization (WHO)-recommended cutoffs. Adjusted with confounding covariates, higher BMI manifested as a positive prognostic predictor. Furthermore, BMI was proven to be associated with the OS in the PS analysis. (UnderweightXtile vs. NormalXtile P = 0.003, OverweightXtile vs. NormalXtile P = 0.019; UnderweightWHO vs. NormalWHO P < 0.001, OverweightWHO vs. NormalWHO P = 0.024). It was also revealed that patients with higher BMI benefitted more from chemotherapy. (Adjusted hazard ratio (aHR): UnderweightXtile vs. NormalXtile vs. OverweightXtile: 0.565 vs. 0.474 vs. 0.409; UnderweightWHO vs. NormalWHO vs. OverweightWHO: 0.613 vs. 0.464 vs. 0.425). Conclusion Among PDAC patients, there was a positive association between BMI and the OS, especially in patients treated with chemotherapy.